Writing Errors and Anosognosia in Amyotrophic Lateral Sclerosis with Dementia - Hiroo Ichikawa; Shinichi Koyama; Hideki Ohno; Kenji Ishihara; Kiyomi Nagumo; Mitsuru Kawamura (Behavioural Neurology)
Amyotrophic lateral sclerosis (ALS) with dementia (ALS-D) is known to exhibit characteristics of frontotemporal dementia. However, in clinical situations, it is often difficult to evaluate their cognitive functions because of impaired voluntary speech and physical disabilities. In order to identify characteristic and diagnostic cognitive symptoms of relatively advanced ALS-D patients, we retrospectively reviewed the clinical features of seven cases of clinically definitive ALS who had dementia, impaired voluntary speech, and physical disability. Their medical records showed that six out of seven patients made writing errors, and all of the patients demonstrated anosognosia. The writing errors consisted of paragraphia such as substitution, omission, or syntactic errors with individual differences in error types. Dissociation between kana and kanji were also observed. Anosognosia was evaluated by a self-rating scale with which the patients and the medical staff evaluated the patient's physical ability; the results indicated a large discrepancy between the evaluation by the patients and the medical staff. We emphasize that aphasic writing errors have been underestimated, particularly in ALS-D patients with impaired voluntary speech. We also reported that anosognosia was the most important and quantifiable symptom in ALS-D. The relationship between writing errors and anosognosia should be investigated further.